Associations between indicators of lipid and glucose metabolism and hypothyroidism - Xinyi Huang; Hengzheng Cheng; Shuting Wang; Laifu Deng; Jiaxiu Li; An Qin; Chunqiang Chu; Xiao Liu (Lipids in Health and Disease)
Abstract Background Hypothyroidism, a prevalent thyroid hormone abnormality identified by biochemical indicators, is prone to serious consequences because of its insidious clinical manifestations and easy underdiagnosis. This research aimed to elucidate the relationships between indicators of lipid and glucose metabolism and hypothyroidism and to assess the value of metabolic indicators for hypothyroidism. Methods Prevalence surveys were conducted utilizing information from 3254 NHANES individuals who passed screening between 2007 and 2012. Comparisons of baseline characteristics, assessment of logistic regression and subgroup analyses, visualization of restricted cubic splines curves, and validation of causal mediation analyses were performed to obtain a comprehensive view of the relationships between indicators of lipid and glucose metabolism and hypothyroidism. Results Lipid and glucose metabolism indicators, especially the unconventional parameters triglyceride‒glucose index (TyG) and remnant cholesterol (RC) and the conventional parameter triglyceride (TG), exhibited robust positive relationships with hypothyroidism and served as crucial mediators in the pathways by which hypothyroidism affects health outcomes. Indicators were varying suggestive for hypothyroidism in distinct populations, with TyG being relatively more valuable. Conclusions Indicators of lipid and glucose metabolism (TyG, TG, and RC) were intimately associated with hypothyroidism, with potential applications in the assessment and management of hypothyroidism.